2020
DOI: 10.1007/s00784-020-03400-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet-rich fibrin for the treatment of gingival recessions: a systematic review and meta-analysis

Abstract: The use of platelet-rich fibrin (PRF) membranes has been shown to additionally improve the clinical outcomes of root coverage in Miller Class I and II gingival recessions compared to the use of coronally advanced flap (CAF) alone. No change in keratinized mucosa width (KMW) or reduction in pocket depths was reported. Compared to the CAF+connective tissue graft (CTG) group, a statistically significant increase in root coverage (RC) and KWM was observed in the CAF+CTG group. No differences between PRF and EMD or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 59 publications
2
45
0
2
Order By: Relevance
“…Furthermore, an array of different surgical procedures utilized to treat IBDs exists. Previously, it was shown that great variability in surgical approaches was discussed when PRF was used for the treatment of gingival recessions [75]. Future research investigating more precisely various surgical difference such as flap design and surgical techniques (e.g., MIST and M-MIST) should be further evaluated in future studies to better determine optimal surgical approaches when using PRF in regenerative therapy of IBDs.…”
Section: Implications For Clinical Practice and Future Directionmentioning
confidence: 99%
“…Furthermore, an array of different surgical procedures utilized to treat IBDs exists. Previously, it was shown that great variability in surgical approaches was discussed when PRF was used for the treatment of gingival recessions [75]. Future research investigating more precisely various surgical difference such as flap design and surgical techniques (e.g., MIST and M-MIST) should be further evaluated in future studies to better determine optimal surgical approaches when using PRF in regenerative therapy of IBDs.…”
Section: Implications For Clinical Practice and Future Directionmentioning
confidence: 99%
“…Solid platelet-rich fibrin (PRF), which is basically the coagulated plasma-rich fraction of blood upon centrifugation, was introduced as a local therapy to support wound healing and potentially also tissue regeneration in oral indications including treatment of gingival recessions (12), increasing the width of keratinized mucosa around implants (13), to prevent atrophic bone resorption following tooth extraction (14), and to lower the symptoms that come along with inflammation such as pain and swelling upon third molar surgery (15). Support for the beneficial clinical performance of PRF application comes from in vitro studies showing that lysates of PRF membranes are capable of reducing the LPS-induced inflammatory response of macrophages indicated by an M1-to-M2 shift of IL6 and arginase 1 expression, respectively (16,17), and also reduce the formation of osteoclasts in murine bone marrow cultures shown by histochemical staining of TRAP and the reduced expression of the respective gene and cathepsin K (18).…”
Section: Introductionmentioning
confidence: 99%
“…underlined the fact that the use of PRF appeared to improve patient-related outcomes such as postsurgical discomfort and pain. 8 …”
Section: Discussionmentioning
confidence: 99%